A study on improved methods in Micro-electromechanical systems technology. (2021) - Aditya Khatokar, J.; Vinay, N.; Sudhir Bale, Ajay; Nayana, M.A.; Harini, R.; Suhaas Reddy, V.; Soundarya, N.; Satheesha, T.Y.; Shivashankar Huddar, A.
Abstract: This current review describes the various micro fabrication techniques, the reliability view of various processes and the various problems that are caused during these processes. This study also emphasizes some of the new device design features. Many parameters that affect and are responsible for these processes are discussed here. The micromachining processes like surface, bulk, LIGA are studied. The study of miniaturization in Micro-electro-mechanical systems (MEMS) is studied in this paper. The advantages of various actuation and their limitations in certain conditions are highlighted. The methods to overcome creep, and to reduce Stiction is presented in detail. The best choice available to print ink with good quality is also highlighted in this paper.